Fatigue failure analysis of fillet welded joints used in Offshore structures using numerical methods. (2021) - Karthik, S; Mahendramani, G
Abstract: In this article, an attempt is made to measure the temperature at the interface between bit and rock samples were Offshore structures have various parts and components that are temporary or not considered to be part of the structure. Offshore structure platform design and construction are a hybrid of steel structure design and harbor design and construction. A welding joint is a point or edge where two or more pieces of metal or plastic are joined together. They are formed by welding two or more workpieces (metal or plastic) according to a particular geometry. The purpose of this project will to provide the designer with an improved knowledge of different fatigue calculation methods used in the maritime industry today, with the aim of decreasing the probability of failure with a higher control of a fatigue failure site. To provide an overview of the different fatigue calculation methods, a comparison study was performed, as well as a local weld parameter study for two fillet welded joints.